(untitled) (Bangladesh Journal of Medicine, 2021)
Background: Dengue is a major international health concern that is prevalent in tropical and sub tropical countries. Study of dengue infection and its Liver complications are scarce from countries like India. This study was done to assess the frequency and spectrum of liver dysfunction and bleeding morbidity in Dengue infection patients. Methods: A Cross sectional prospective observational study was performed in the of Department of Medicine Sir Salimullah Medical College Mitford Hospital. All the inpatients who were diagnosed with dengue infection between July 2015 to July 2016 were included in this study. A total of 70 patients were included in the study. Results: Patients were classified as classical dengue fever (DF) 61.5.% dengue haemorrhagic fever (DHF) 38.5%. The mean age was 28.607±10.45 years in DF group and 26.78±11.78 years in DHF group and male: female ratio was 3:1. Deranged serum glutamic-oxaloacetic transaminase (SGOT) and/or Serum glutamic pyruvic transaminase (SGPT) was present in most of the patients. Elevation of ALT level occured more in DHF group patient (81%) than DF group (46%). Out of 70 patient 28(40%) patient were within normal value. 42 (60%) patient had elevated ALT level which is statistically significant (p value-<0.05)..The degree of rise of SGOT, SGPT,and Bilirubin was significantly more in DHF and DSS, as compared to DF. About bleeding morbidity, purpura was a mentionable finding 29(41%) but gum bleeding 15(21%), echymosis 14(20%), are less in both DF and DHF group. Major bleeding like hematomesis 5 (7%), melaena 4 (5%) and haematuria 1 (1%) also occured in both group of patients. Conclusion: Liver dysfunction in the form of raised SGPT was seen in almost all patients. Preferentially high SGOT may serve as an early indicator of dengue infection while high values of bilirubin, SGOT, SGPT,may be an indicator of severe disease and poor prognosis. Bangladesh J Medicine July 2022; 33(1) : 44-51